Análisis de los gastos económicos ejecutados por la Municipalidad Provincial de Maynas, periodo 2017 - 2020 - Panduro Ramirez, Ara Abigail (2022)
The economic expenses executed by the Provincial Municipality of Maynas, are necessary so that it can comply with the activities programmed in its Institutional Strategic Plan, and with it, be able to meet the needs of the population in order to improve their quality of life through the different activities in order to improve their quality of life through the different activities to be developed, as well as promoting public investment through the execution of public expeditures. The title of this research is "Analysis of the economic expenses executed by the Provincial Municipality of Maynas, period 2017-2020”, its general objective was to determine the behavior of the economic expenses executed by the Provincial Municipality of Maynas in the period 2017 to the 2020. Likewise, the research was of a quantitative type and of a descriptive, non-experimental - cross-sectional design. From the analysis and discussion of the results obtained, it was possible to determine that the economic expenses show a behavior with a positive trend in the study period.